Assessing the estrogenic activity of chemicals present in resin based dental composites and in leachates of commercially available composites using the ERα-CALUX bioassay. Issue 12 (December 2021) - Boonen, Imke; De Nys, Siemon; Vervliet, Philippe; Covaci, Adrian; Van Landuyt, Kirsten L.; Duca, Radu Corneliu; Godderis, Lode; Denison, Michael S.; Elskens, Marc
Abstract: Objective: The biocompatibility of resin based dental composites has not yet been fully characterized even though certain monomers used in these composites are synthesized from Bisphenol A (BPA), a well-known estrogenic endocrine disruptor. As a result, they show structural relationship to BPA and can contain it as an impurity. Therefore, the estrogenic activity of 9 monomers, 2 photoinitiators, one photostabilizer and leachates of 4 commercially available composites was determined. Methods: The ERα-CALUX bioassay was used to determine both agonistic and antagonistic estrogenic activities of the pure compounds (BPA, BisDMA, BisGMA, BisEMA(3), BisEMA(6), BisEMA(10), TEGDMA, TCD-DI-HEA, BADGE, UDMA, HMBP, DMPA, CQ) and the leachates of cured composite disks. The leachates of 4 commercially available composites (Solitaire 2, Ceram.x Spectra ST, G-ænial Posterior and Filtek Supreme XTE) in water and 0.1 M NaOH (pH = 13, 'worst-case scenario') were tested for estrogenic activity (pooled leachates from 10 cured composite disks). Results: Agonistic estrogenic activity was found for the monomer BisDMA, the photostabilizer HMBP and photoinitiator DMPA. All leachates from the 4 tested composites showed significant agonistic estrogenic activity higher than the DMSO control, and the highest activity (potency and efficacy) was found for Solitaire 2, followed by Ceram.x Spectra ST. Furthermore, antagonistic estrogenic activity was found in the leachates from G-ænial Posterior. Significance: These results show that significant estrogenic activity was found in all leachates of the cured composite disks, and that this estrogenicity is most likely due to a mixture effect of multiple estrogenic compounds (including BPA, HMBP and DMPA). This indicates that further research into the endocrine activity of all the compounds that are present in these composites (even at low quantities) and their possible mixture effect is warranted to guarantee their safe use.